2015
DOI: 10.3390/g6040574
|View full text |Cite
|
Sign up to set email alerts
|

Commitment to Cooperation and Peer Punishment: Its Evolution

Abstract: Theoretical and empirical studies have generally weighed the effect of peer punishment and pool punishment for sanctioning free riders separately. However, these sanctioning mechanisms often pose a puzzling tradeoff between efficiency and stability in detecting and punishing free riders. Here, we combine the key aspects of these qualitatively different mechanisms in terms of evolutionary game theory. Based on the dilemmatic donation game, we introduce a strategy of commitment to both cooperation and peer punis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 43 publications
0
36
0
Order By: Relevance
“…The problem of explaining the emergence of collective behavior has been studied extensively from a wide range of research fields, including Anthropology, Sociology, Economics, Evolutionary Biology, Psychology, and, more recently, Artificial Intelligence (AI) and Multiagent Systems (MAS) [1,3,16,17,20,22,24,29,33,37,41,46,50,54,69,71]. The PGG is a standard framework to study this problem, as it captures the tension between the benefit of mutual cooperation and the temptation to exploit the efforts of others in a joint venture [13,31,43,49,56,70].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…The problem of explaining the emergence of collective behavior has been studied extensively from a wide range of research fields, including Anthropology, Sociology, Economics, Evolutionary Biology, Psychology, and, more recently, Artificial Intelligence (AI) and Multiagent Systems (MAS) [1,3,16,17,20,22,24,29,33,37,41,46,50,54,69,71]. The PGG is a standard framework to study this problem, as it captures the tension between the benefit of mutual cooperation and the temptation to exploit the efforts of others in a joint venture [13,31,43,49,56,70].…”
Section: Related Workmentioning
confidence: 99%
“…Another commitment experiment [10] takes the form of a deposit and refund scheme [50]: In this scheme, players that agree to commit have to deposit an amount which will be refunded only if they honor the commitment and contribute to the common good. The main difference with our analysis is that the agreement is set up exogenously by a third party instead of being implemented as a strategic behavior (i.e.…”
Section: Related Workmentioning
confidence: 99%
“…It can be understood such that players make a commitment before the game is actually played. Recently, a series of papers analyzed the effect of such pre-commitments on evolution of cooperation (Han et al, 2013(Han et al, , 2015a(Han et al, ,b, 2017aSasaki et al, 2015;Han and Lenaerts, 2016) and found that pre-commitments were effective in enhancing cooperation. Those works typically assume that players can choose whether they make a costly commitment before the game.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, this poses a second---order free rider problem-freeloading on others' efforts in making responsible punishment or assessments undermines the equilibrium of Punishers and Discriminators [44,64]. To address this problem, some solutions have been presented to date such as pool punishment with second---order punishment [65] and the punitive deposit system [66,67]. In indirect reciprocity, Sasaki and colleagues recently explored pre---assessment systems to detect second---order free riders [45].…”
Section: Discussionmentioning
confidence: 99%